2015
DOI: 10.1039/c4nr05988c
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4 nanoparticles decorated carbon nanofiber mat as binder-free air-cathode for high performance rechargeable zinc-air batteries

Abstract: An efficient, durable and low cost air-cathode is essential for a high performance metal-air battery for practical applications. Herein, we report a composite bifunctional catalyst, Co3O4 nanoparticles-decorated carbon nanofibers (CNFs), working as an efficient air-cathode in high performance rechargeable Zn-air batteries (ZnABs). The particles-on-fibers nanohybrid materials were derived from electrospun metal-ion containing polymer fibers followed by thermal carbonization and a post annealing process in air a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
145
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(152 citation statements)
references
References 56 publications
4
145
0
3
Order By: Relevance
“…[7] Some of them, such as NiCo 2 O 4, [8] C-CoPAN900, [9] CoS x /NS-GN, [10] and (CoO/N-CNTs + NiFe-LDH/CNT) [11] have been further implemented into real air cathodes for rechargeable zinc-air batteries.T hose catalysts that solely contain oxides generally show low activity owing to their self-accumulation and insufficient electrical conductivity. [12] It was believed that combining metal oxides and conductive nanocarbon materials such as graphene and carbon nanotubes is an effective approach to enhancing catalytic activity of oxides, [5,13] through increasing number of available active sites and providing efficient charge transport channels.…”
mentioning
confidence: 99%
“…[7] Some of them, such as NiCo 2 O 4, [8] C-CoPAN900, [9] CoS x /NS-GN, [10] and (CoO/N-CNTs + NiFe-LDH/CNT) [11] have been further implemented into real air cathodes for rechargeable zinc-air batteries.T hose catalysts that solely contain oxides generally show low activity owing to their self-accumulation and insufficient electrical conductivity. [12] It was believed that combining metal oxides and conductive nanocarbon materials such as graphene and carbon nanotubes is an effective approach to enhancing catalytic activity of oxides, [5,13] through increasing number of available active sites and providing efficient charge transport channels.…”
mentioning
confidence: 99%
“…Co 3 O 4 -Nanostäbchen zeigen eine hçhere Aktivität in der ORR als NPs, [77] was dadurch verursacht wird, dass die Nanostäbchen eine hçhere Oberflä-chendichte von exponierten Co 3+ -Ionen bieten. Es wurde eine Reihe von Cobaltoxiden mit komplexen Nanostrukturen hergestellt, einschließlich geordneter mesoporçser, [78] Kern/ Schale-, [79][80][81] und hohler Architekturen, [82,83] [84] CNTs [85,86] und Graphen gekoppelt werden. [87,88] Einzelheiten hierzu folgen später.…”
Section: Metalloxideunclassified
“…Hor, Liu, and Zong et al reported an integrated bifunctional catalyst electrode of bifunctional catalytically active Co 3 O 4 NPs decorated CNFs as an efficient O 2 -cathode in high-performance rechargeable Zn-O 2 batteries. [292] The 3D nanohybrid material is prepared by the electrospinning mixture solution of selected polymers and metal salts followed by a thermal treatment and a post annealing process in air at a moderate temperature. The investigation results demonstrate that the nanohybrid material effectively catalyzes ORR via an ideal 4-electron transfer process and outperforms Pt/C toward catalyzing OER in alkaline aqueous electrolyte.…”
Section: Metal-o 2 Batteriesmentioning
confidence: 99%